Pengaruh Corporate Social Responsibility terhadap Konservatisme Akuntansi dengan Kepemilikan Negara sebagai Variabel Moderasi Pada Perusahaan Sektor Energi dan Sektor Basic Materials Terdaftar di BEI Periode 2020-2022 - Kristanti Diyah Anggraini; Haris Wibisono; Intan Immanuela (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2024)
This research aims to examine the influence of CSR on accounting conservatism and to test state ownership as a moderator of the influence of CSR on accounting conservatism. The research focuses on companies in the energy and basic materials sectors listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. Data sources were obtained from annual reports, sustainability reports from the official websites of the sampled companies, and the IDX official website. The sampling technique used purposive sampling based on specific criteria, resulting in a selection of 45 samples. Data analysis employed multiple linear regression. The results of this study indicate that the disclosure of CSR has a negative effect on accounting conservatism, and state ownership does not moderate the influence of CSR on accounting conservatism.